Identification of Constraints in Adoption of Improved Dairy Farming Practices in Bundi District of Rajasthan (Indian Journal of Extension Education, 2016)
Dairying has been recognized as a remunerative source of income in India. But the productivity of dairy animals is very low. Despite widespread availability, adoption of these technologies in the dairy farming has been relatively sparse so far. The adoption of recommended dairy farming practices, therefore, becomes a pre-requisite for sustained growth and development of dairy farming. But low adoption of modern dairy farming technologies amongst farmers has been identified as one of the main reasons for the low productivity in the country. Realizing the fact present study was undertaken with the objective to gain new insight into constraints in adoption of improved dairy farming practices. The study was conducted in Bundi district of Rajasthan. Results of study showed that lack of knowledge, poor extension support, poor credit support, lack of proper communication system, non-availability of desired technology, complexity of practices, high cost of inputs, and lack of conviction were the major constraints perceived by farmers in adoption of improved dairy farming practices.